Acute Ablation of Cortical Pericytes Leads to Rapid Neurovascular Uncoupling - Kisler, Kassandra; Nikolakopoulou, Angeliki M.; Sweeney, Melanie D.; Lazic, Divna; Zhao, Zhen; Zlokovic, Berislav V. (Frontiers in Cellular Neuroscience, 2020)
Pericytes are perivascular mural cells that enwrap brain capillaries and maintain blood brain barrier integrity. Most studies suggest that pericytes regulate cerebral blood flow (CBF) and oxygen delivery to activated brain structures, known as neurovascular coupling. While we have previously shown that congenital loss of pericytes leads over time to aberrant hemodynamic responses, the effects of acute global pericyte loss on neurovascular coupling have not been studied. To address this, we used our recently reported inducible pericyte-specific Cre mouse line crossed to iDTR mice carrying Cre-dependent human diphtheria toxin (DT) receptor, which upon DT treatment leads to acute pericyte ablation. As expected, DT led to rapid progressive loss of pericyte coverage of cortical capillaries up to 50% at 3 days post-DT, which correlated with approximately 50% reductions in stimulus-induced CBF responses measured with laser Doppler flowmetry and/or intrinsic optical signal imaging. Endothelial response to acetylcholine, microvascular density, and neuronal evoked membrane potential responses remained, however, unchanged, as well as arteriolar smooth muscle cell (SMC) coverage and functional responses to adenosine, as we previously reported. Together, these data suggest that neurovascular uncoupling in this model is driven by pericyte loss, but not other vascular deficits or neuronal dysfunction. These results further support the role of pericytes in CBF regulation, and may have implications for neurological conditions associated with rapid pericyte loss such as hypoperfusion and stroke, as well as conditions where the exact time course of global regional pericyte loss is less clear, such as Alzheimer’s disease and other neurogenerative disorders.